As políticas públicas e o problema da concretização dos direitos quilombolas no Brasil: o exemplo Kalunga - Dalosto, Cássius Dunck (2016)
This dissertation has as object of analysis the current public politics from the federal government destined to Brazilian quilombo communities. A study on what were the quilombo communities and their legal concept during the colonial period and also on the redefinition process of the concept of quilombo on that period to the present day is done. Therefore, this is the process of fighting of the former captives and also the black population and free mixed race from the time of the Empire to the present day, particularly against racism and against the blockade of access to land imposed by the State, as well as the genealogy of Art. 68 from the Acts of the Constitutional Transitional Dispositions and public policy from the federal government intended for these communities. It discusses about the effectiveness of these federal public policies within the social reality, seeking to identify major problems in its implementation, especially in the Kalunga quilombo community, which is used as a case study.